Correction: Graphene oxide–TiO2 composite: an efficient heterogeneous catalyst for the green synthesis of pyrazoles and pyridines. (21st October 2019) - Kumari, Shweta; Shekhar, Amiya; Pathak, Devendra D.
Abstract : Correction for 'Graphene oxide–TiO2 composite: an efficient heterogeneous catalyst for the green synthesis of pyrazoles and pyridines' by Shweta Kumari et al., New J. Chem., 2016, 40, 5053–5060.